Słownictwo dawne w korespondencji rodzinnej Zofii Kossak – rekonesans badawczy - Nowak, Małgorzata (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2024)
This article aims to answer the research question about the place of dated lexis in Zofia Kossak’s private idiolect as evidenced in her family correspondence. The research corpus collected for the analysis consisted of 607 letters, written between 1946 and 1968, and addressed to her daughter Anna and son Witold as well as her children’s spouses and their children. The lexical units classified as obsolete were marked through contrastive analysis and verified against the Dictionary of Polish Language edited by Witold Doroszewski (SJPDor). The study allows for drawing the conclusion that in the vivid natural language used by Kossak, dated lexical stock occupied anything but a marginal position (a total of 69 words were extracted from the research material qualified in SJPDor as obsolete or dated, e.g.: afekt [affect, emotion, love], dezolacja [desolation], felicytacja [congratulations, wishing well], hołdownik [derog. worshipper], rankor [anger, indignance or grief], oprymować [oppress], rewokować [revoke], maluczko [close shave] and 13 other dated morphological structures of the type tysiącolecie (reg. pl. tysiąclecie [millennium]), dokumenta (reg. pl. dokumenty [documents]). The presented list of lexemes is only an approximation. The main limitation of the reported research, related to the methodological assumptions it rests on, is that the vocabulary acquired the status “dated” in the mid- 20th century, but it was not marked with a chronological qualifier in SJPDor.